Complete tissue coverage achieved by scaffold-based tissue engineering in the fetal sheep model of Myelomeningocele. (January 2016) - Watanabe, Miho; Li, Haiying; Kim, Aimee G.; Weilerstein, Aaron; Radu, Anteneta; Davey, Marcus; Loukogeorgakis, Stavros; Sánchez, Melissa D.; Sumita, Kazutaka; Morimoto, Naoki; Yamamoto, Masaya; Tabata, Yasuhiko; et al.
Abstract: Myelomeningocele (MMC) is the most severe form of spina bifida, one of the most common congenital anomalies. Although open fetal surgical repair of the MMC defect has been shown to result in improved outcomes, a less invasive approach applicable earlier in gestation than the current open surgical approach between 19 and 26 weeks of gestation is desirable for further improvement of neurological symptoms, as well as reduction of maternal and fetal risks. We previously reported the therapeutic potential of a scaffold-based tissue engineering approach in a fetal rat MMC model. The objective of this study was to confirm the long-term efficacy of this approach in the surgically created fetal sheep MMC model. Gelatin-based or gelatin/collagen hybrid sponges were prepared with and without basic fibroblast growth factor (bFGF) incorporation. The defect was covered by a sponge and secured by a supporting sheet with adhesive at 100 days of gestation or the gelatin/collagen hybrid with bFGF was secured with adhesive without the sheet. Although sheets were found detached at term (140 days' gestation), both gelatin-based and gelatin/collagen hybrid sponges had integrated within the newly formed granulation tissue, resulting in complete coverage of the MMC defect. The release of bFGF from sponges resulted in enhanced formation of granulation tissue and epithelialization. There was also evidence of improved preservation of the spinal cord with less associated damage on histological analysis and reversal of hindbrain herniation. These experiments provide important proof-of-principle evidence of the efficacy of scaffold-based tissue engineered coverage for the prenatal treatment of MMC.